Localized phase transformation strengthening in CoNi-based superalloys - Bezold, Andreas; Egan, Ashton; Völkl, Julian; Karpstein, Nicolas; Gaag, Tobias; Spiecker, Erdmann; Göken, Mathias; Mills, Michael J.; Neumeier, Steffen (Scripta Materialia, 2025)
Segregation processes during high-temperature deformation can be either detrimental or beneficial in γ′-strengthened superalloys depending on which elements segregate. In intermediate CoNi-based superalloys only softening due to extensive microtwinning was observed so far. By analyzing the creep behavior of a Ta-free and a Ta-containing CoNi-based superalloy at 750 °C and 620 MPa, we show that strengthening segregation behaviors along various planar defects, including microtwinning, can be achieved in this alloy class. While both alloys deformed under planar fault formation, the Ta-containing alloy outperformed the Ta-free alloy. Atomic-scale energy dispersive spectroscopy investigations revealed strengthening effects by local phase transformations along superlattice intrinsic and extrinsic stacking faults in both alloys. However, microtwinning is enhanced in the Ta-free alloy, while it is impeded in the Ta-containing alloy. Given the faster diffusivity of Ta compared to W, kinetic effects on localized phase transformation strengthening and their subsequent influence on the creep behavior are discussed.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Creep; Segregation; Stacking fault; Superalloy; Transmission electron microscopy

Stress-dependent χ phase transformation in a Ni-based superalloy - Egan, Ashton; Gunda, N. S.Harsha; Feng, Longsheng; Ghazisaeidi, Maryam; Wang, Yunzhi; Tin, Sammy; Mills, Michael J. (Communications Materials, 2025)
The ongoing push to elevate operating temperatures in aerospace gas turbine engines – driven by goals of enhanced fuel efficiency and reduced CO2 emissions – mandates advancements in the creep resistance of Ni- and Co-based superalloys, which are integral for critical engine components. This study elucidates the role of stress assisted localized phase transformations in the creep properties of these alloys. By leveraging chemo-mechanical coupling, self-healing γ′ precipitates are designed to immobilize planar defects, thereby increasing creep resistance. Employing advanced characterization techniques such as high-resolution Scanning Transmission Electron Microscopy (HR-STEM), in conjunction with atomistic simulations and thermodynamic calculations, novel deformation pathways facilitated by χ local phase transformation (LPT) strengthening have been uncovered; notably, the formation of χ nano-laths through microtwinning and superlattice intrinsic stacking fault (SISF) shearing. This study highlights critical insights into the compositional boundaries necessary for optimizing LPT strengthening while avoiding deleterious bulk formation of η/χ phases. These advancements will guide the design of new alloys maximizing high-temperature creep strength for advanced aerospace applications.
CRIS-Team Scopus Importer:2025-08-29